Venezuelan migrants in Camana, motivation and migratory project - Cárdenas Hinojosa, Patricio Manolo (2021)
The present investigation was carried out in order to deepen the motivations of the migratory flow of Venezuelans in the city of Camaná, department of Arequipa, the investigative context, revolved around the approach of economic sciences, specifically the motivation and migratory project , all of this under a quantitative approach, with a non-experimental design and categories validated by qualitative research, from these evidences we have that migratory networks and families, allow to condition a migratory project, by virtue of benefits and maximization, weighing the transfer and adaptation costs in the district of Camaná, department of Arequipa, Peru.